Dyspozycje aksjologiczne nauczyciela – perspektywa ucznia - Czapla, Małgorzata (Kultura-Społeczeństwo-Edukacja, 2021)
The articles justifies the need for constant care for the axiological dimension of education. The habitus of the modern teacher was analyzed in the perspective of axiological dispositions. The author’s reconstructions of the respondents’ views concerning their preferences regarding observable and repetitive teachers’ behavior were categorized. These behaviors were indicators of the values which guided teachers in their work with students. An attempt was made to determine which axiological properties of teachers, expressed in the praxiological dimension, are particularly valued by today’s youth. Analysis of the frequency of indications of the preferred teachers’ behaviors helped to establish the hierarchy of these properties. The results of the diagnosis carried out on a sample of 903 respondents showed that teachers’ pedagogical tactfulness, subject knowledge and good organization of work are mostly appreciated and expected by young people. In addition, attempts were made to identify differences in the respondents’ preferences due to their interest profile, expressed in the choice of a specific field of academic studies. It has been established that it is the factor which differentiates students’ preferences in relation to the teacher’s axiological attributes. Significant relationships have been observed and the conclusions made valuable implications for pedeutology.